Stability of vortex rotation around a mesoscopic square superconducting ring under radially injected current and an external magnetic field. (23rd February 2017) - Xue, Cun; He, An; Li, Chun; Zhou, Youhe
Abstract: We present the stability of vortex rotation around a mesoscopic square superconducting ring under radially injected currents and external magnetic fields based on time-dependent Ginzburg–Landau equations. We demonstrate that the vortex rotation around a square ring can lead to voltage oscillations as the vortices periodically pass by the corners. The amplitude of the time evolution of the voltage oscillations as a function of external current is studied at different magnetic fields, and the effect of thermal noise on the voltage oscillations is discussed. The rotation frequency depends linearly on external current at lower magnetic fields, whereas it is a nonlinear function of external current at higher magnetic fields. The stable vortex rotation appears in a certain range of injected currents under magnetic fields, but it is unstable at high injected currents. It is found that such a transition from stability to instability can lead to an abrupt jump in current–voltage characteristics.